Inter- and Intramolecular [2+2+2] Cycloaddition of Alkyne Triple Bonds to the Carbonyl Function of Aldehydes and Ketones Enabled by η5-Cyclopentadienylcobalt(L)(L′) - Colovray-Gotteland, Véronique; Harvey, Daniel F.; Johnson, Barry M.; Ung, Christopher S.; Vollhardt, K. Peter C. (Synthesis, 2020)
1,7-Octadiyne underwent [2+2+2] cycloaddition to acetone in the presence of η5-cyclopentadienylcobalt(L)(L′) complexes to give (η5-cyclopentadienyl)[(1,4,4a,8a-η4)-5,6,7,8-tetrahydro-3,3-dimethyl-3H-2-benzopyran]cobalt, in which the two triple bonds and the carbonyl moiety have combined to engender a 2H-pyran ring complexed to CpCo. The scope of this reaction was explored, including cocyclizations of ynals and ynones with bis(trimethylsilyl)acetylene, as well as all-intramolecular reorganizations of α,ω-diynals and -diynones. Two major trajectories were observed in the case of aldehydes, the (often minor) [2+2+2] pathway and a competing trail featuring a formal 1,5-hydride shift that results in CpCo–dienones. The latter is obviated for ketone substrates. Preliminary chemistry of selected complexes uncovered unprecedented reactions, such as acid-catalyzed ring openings and additions of amines, the latter providing access to novel carbon frames.
Keywords: alkynes; carbonyl compounds; cobalt; cycloaddition; 2H-pyrans